Improving care for intimate partner violence in the emergency department: recommendations from a Canadian retrospective chart review - Duchesne, Emma; Ross, Alison N.; Lewis, Jane; Bartels, Susan A.; Walker, Melanie; Rocca, Nicole (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background Intimate partner violence (IPV) is prevalent among patients visiting the emergency department (ED). Studies show that patients experiencing IPV continue to have negative care experiences in the ED, leading to an increased risk of adverse physical, mental, legal, and economic outcomes. However, few studies explore ED care metrics and gaps in knowledge on how providers can improve. Methods We sought to fill these gaps by collecting quantitative and qualitative electronic data on ED care parameters for patients experiencing IPV. A retrospective chart review was conducted for patients seen in our tertiary care center’s ED and by our Sexual Assault and Domestic Violence Program between December 17, 2018 and June 16, 2021. Quantitative data, including sociodemographics, were summarized using medians/interquartile ranges and frequencies/proportions as appropriate using SPSS. This paper describes IPV care metrics across three domains: (1) ED mandatory reporting, (2) medical management of strangulation, and (3) discharge diagnosis containing IPV. Additionally, when documenting IPV encounters in charts, the use of trauma- and violence-informed care (TVIC) principles was evaluated as a secondary exploratory outcome. Results A total of 124 clinical encounters were analyzed. Among these, 54 involved children in the home, and documentation of mandatory reporting was absent in 43% (23/54) of such cases. Twenty-five patients experienced strangulation; however, 88% (22/25) of these cases were inadequately investigated. Furthermore, IPV was omitted as a discharge diagnosis in 38% (47/124) of encounters. Overall, 64% (79/124) of charts demonstrated a lack of trauma- and violence-informed care (TVIC) principles in the documentation of IPV-related encounters. Conclusions These findings highlight that gaps exist for ED patients experiencing IPV and illuminate areas for improvement of clinical care. We provide evidence-based recommendations for ED providers to improve their management of IPV, including review of mandatory reporting legislation, overview of clinical criteria requiring contrast imaging for strangulation, and discussion around the significance of including IPV in ED discharge diagnosis. Clinical trial number Not applicable.